Perfeksionisme dan Kecemasan: Distingsi antara Sakinah dan Tuma'ninah dalam Al-Qur'an - Afifah Syawalia Arifin; Ade Fakih Kurniawan; Agus Ali Dzawafi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Maladaptive perfectionism intensifies anxiety by imposing rigid internal standards, amplifying fear of failure, and making self-worth contingent upon achievement. This study examines the functional distinction between sakinah and tuma'ninah in the Qur'an as two Qur'anic modes of inner serenity and reconstructs their conceptual relevance for responding to anxiety generated by maladaptive perfectionism. Employing a qualitative library-based design, the study applies the thematic exegetical method (tafsir mawdu'i) and analyzes selected Qur'anic verses through classical and contemporary exegetical works. The findings are then mapped through perfectionism theory as an analytical lens. The study demonstrates that sakinah denotes situational tranquility that stabilizes the inner self in moments of acute emotional pressure, whereas tuma'ninah signifies an enduring and internalized tranquility grounded in faith, dhikr, and acceptance of divine decree. In the context of maladaptive perfectionism, sakinah mitigates the immediate surge of anxiety caused by failure, while tuma'ninah reorients self-worth from achievement-based validation toward the meaning of servitude (ubudiyyah). These findings generate a two-stage model of inner transformation: emotional stabilization followed by the reorientation of self-worth. This model offers a Qur'anic conceptual framework for interpreting the movement from maladaptive perfectionism toward a more adaptive and spiritually integrated form of striving.